If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -1(x + -3) = 7(x + 8) Reorder the terms: 10 + -1(-3 + x) = 7(x + 8) 10 + (-3 * -1 + x * -1) = 7(x + 8) 10 + (3 + -1x) = 7(x + 8) Combine like terms: 10 + 3 = 13 13 + -1x = 7(x + 8) Reorder the terms: 13 + -1x = 7(8 + x) 13 + -1x = (8 * 7 + x * 7) 13 + -1x = (56 + 7x) Solving 13 + -1x = 56 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 13 + -1x + -7x = 56 + 7x + -7x Combine like terms: -1x + -7x = -8x 13 + -8x = 56 + 7x + -7x Combine like terms: 7x + -7x = 0 13 + -8x = 56 + 0 13 + -8x = 56 Add '-13' to each side of the equation. 13 + -13 + -8x = 56 + -13 Combine like terms: 13 + -13 = 0 0 + -8x = 56 + -13 -8x = 56 + -13 Combine like terms: 56 + -13 = 43 -8x = 43 Divide each side by '-8'. x = -5.375 Simplifying x = -5.375
| 28B^2+8B=0 | | 5t^2+37t+72=72 | | 2x^3-6x=-4 | | 8y+7x=-75 | | 2x^3-6c=-4 | | 5x+7(7-8x)=8x-4(8x+8) | | x/5x-4=3 | | 2(x-9)=y-26 | | (4n+5)-(-6n+7)=-15n-302 | | (7x+9)(2x-5)=0 | | 16t^2-164t-36=0 | | 10=a+15 | | 5d^2-30d+40=0 | | 7y+3(y-4)=3(y-1)-2 | | 2(5+2x)-4= | | ln(5x+2)=4.5 | | 23*j-9*j^2=-12 | | 25+x=15-(3x-10) | | 9z^2+36z+25=0 | | 4ln+10lnx=9 | | (4n+5)-(6n+7)=-15n-302 | | 1.2+6=0.2 | | 5x-2(x-3)=-3 | | 3(b+1)=4-1 | | 3y+6=111 | | 14+3(x+4)=38 | | 3z-18=81 | | 5/7=?/56 | | 3z-3=96 | | -4x+3-2x+6=-15 | | -8y-12=3y+22 | | 4ln(5x+2)=18 |